The Correlation between Information Quality and User Satisfaction of the Hospital Management Information System - Suandari, Putu Vierda Lya; Suasnawa, I Gede; Nugraha, I Nyoman Adikarya; Sutrisnawati, Ni Nyoman Dwi (Indonesian Journal of Global Health Research, 2024)
The Hospital Management Information System (HMIS) is a system of communication and information that processes and integrates the entire flow of hospital service in a network of coordination, reporting and administrative procedures to obtain accurate information. Integrated HMIS will help speed up the hospital management process. Purpose: To determine the correlation between the quality of information produced by HMIS and user satisfaction in terms of the benefits generated at Balimed Hospital Denpasar. Methods: This research used a quantitative method by administering a questionnaire. The number of samples was 69 respondents HMIS users from 15 unit in the hospital with Proportionate Random Sampling technique. Data was collected using a questionnaire with the sample participating in answering several questions in this research questionnaire. Spearmans Test was conducted for Hypothesis testing. Results: Variable of information quality has good category with overall average value is 2.71. The statement with the highest average value is "HMIS produces accurate information" which is 3.27. The statement with the lowest average value is "how HMIS works is difficult to understand" which is 1.88. Variable of user satisfaction has the satisfied category with overall average value is 2.95. The statement with the highest average value is "the information systems, facilities and equipment currently provided and used, can help and satisfy user" which is 3.27. The statement with the lowest average value is "The information provided is not reliable/trustworthy" which is 2.21. The results of the analysis obtained r value = 0.76 with p value <0.001. These results mean that information quality has a positive and significant effect on user satisfaction.